Endotherapy for paraduodenal pancreatitis: a large retrospective case series - Arvanitakis, Marianna; Rigaux, Johanne; Toussaint, Emmanuel; Eisendrath, Pierre; Bali, Maria Antonietta; Matos, Celso; Demetter, Pieter; Loi, Patrizia; Closset, Jean; Deviere, Jacques; Delhaye, Myriam (Endoscopy, 2014)
Background and study aims: Paraduodenal pancreatitis is histologically well defined but its epidemiology, natural history, and connection with chronic pancreatitis are not completely understood. The aim of this study was to review the endoscopic and medical management of paraduodenal pancreatitis.Patients and methods: Medical records of all patients with paraduodenal pancreatitis diagnosed by magnetic resonance cholangiopancreatography (MRCP) or endoscopic ultrasonography (EUS) between 1995 and 2010 were retrospectively reviewed. Clinical features, imaging procedures, and treatments were investigated. The primary end point was the rate of clinical success, and the secondary end points were the radiological or endoscopic improvement, complication rate, and overall survival rate. Results: A total of 51 patients were included in the study (88.2 % alcohol abuse; median age 49 years [range 37 – 70]; 50 men). The most frequent symptoms at presentation were pain (n = 50; 98.0 %) and weight loss (n = 36; 70.6 %). Chronic pancreatitis was present in 36 patients (70.6 %), and 45 patients (88.2 %) had cysts. Other findings included stricture of the pancreatic duct (n = 37; 72.5 %), common bile duct (n = 29; 56.9 %), and duodenum (n = 24; 47.1 %). A total of 39 patients underwent initial endoscopic treatment: cystenterostomy (n = 20), pancreatic and/or biliary duct drainage (n = 19), and/or duodenal dilation (n = 6). For the patients with available follow-up (n = 41), 24 patients required repeat endoscopy and 9 patients required surgery after the initial endoscopic management. After a median follow-up of 54 months (range 6 – 156 months), complete clinical success was achieved in 70.7 % of patients, and the overall survival rate was 94.1 %. Conclusions: This is the largest series concerning the management of paraduodenal pancreatitis using endotherapy as the first-line intervention. Although repeat endoscopic procedures were required in half of the patients, no severe complication was observed and surgical treatment was ultimately needed in less than 25 % of the patients.